PENGARUH PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2), BEA PEROLEHAN HAK ATAS TANAH (BPHTB), DAN PAJAK AIR TANAH TERHADAP PENDAPATAN ASLI DAERAH (Studi pada Pemerintah Kabupaten/Kota di Provinsi Jawa Tengah Tahun 2020-2024) - Alvia Dwi Fitriana; Haryanto Haryanto (Diponegoro Journal of Accounting, 2025)
This study aims to analyze the effect of PBB-P2, BPHTB, and Groundwater Tax on Local Own-Source Revenue (PAD). The variables used in this study are local own-source revenue as the dependent variable, while PBB-P2, BPHTB, and Groundwater Tax serve as the independent variables.The data source used in this study is secondary data in the form of panel data. The population used is all regions in Central Java Province from 2020 to 2024. The population includes 35 regions, while the sample was 175 obtained from 35 districts/cities multiplied by 5 years. The sample was selected using a saturated sampling method. The analysis method employed in this research is multiple linear analysis using SPSS version 27.The results of the study showed that Rural and Urban Land and Building Taxes (PBB-P2) and the Land and Building Rights Acquisition Duty (BPHTB) have a positive and significant effect on Local Own-Source Revenue (PAD). Meanwhile, the Groundwater Tax does not have a significant effect on local revenue.